When Antlers Grow Abnormally: A Hidden Disease Behind Common Cervid Trophy Deformities, Introducing Pedunculitis Chronica Deformans - Sükösd, Farkas; Lakatos, István; Ürmös, Ádám; Karkas, Réka; Sükösd, Ákos; Palánki, Gábor; Arany Tóth, Attila; Erdélyi, Károly; Misó, Mihály; Gőbölös, Péter; Posta, Katalin; Kovács, Ferenc; et al. (Animals (Basel), 2025)
For centuries, the most prevalent antler abnormalities observed worldwide have been attributed to trauma. However, detailed pathological investigation of these cases has not yet been carried out. In free-living fallow deer (Dama dama), we identified a chronic osteomyelitis-like condition—Pedunculitis Chronica Deformans (PCD)—using pathological and radiological diagnostics. We propose that inflammation during post-casting wound healing and consequent scar formation can trigger the development of PCD. In this study, we characterize the pathomorphology of PCD and introduce a scoring system to describe its severity. Furthermore, we describe the histoanatomy of the junction between the pedicle and the surrounding skin—an area essential for the integrity of the integument—which, when compromised, may predispose cervids to PCD. Our findings suggest that the most common antler abnormality results from a pathological fracture associated with PCD, which can be further complicated by fatal meningoencephalitis and brain abscesses. PCD-related lesions, while less frequently observed, can also be identified in roe deer (Capreolus capreolus) and red deer (Cervus elaphus), with species-specific differences. These findings overlap with cases reported in other cervid species, suggesting a more general disorder of antler formation. Describing this condition provides a basis for assessing its epidemiology and understanding its relevance to wildlife health.